2019
DOI: 10.1186/s13256-019-2056-1
|View full text |Cite
|
Sign up to set email alerts
|

Distal renal tubular acidosis and severe hypokalemia: a case report and review of the literature

Abstract: Background Distal renal tubular acidosis is a relatively infrequent condition with complex pathophysiology that can present with life-threatening electrolyte abnormalities. Case presentation We describe a case of a 57-year-old Caucasian woman with previous episodes of hypokalemia, severe muscle weakness, and fatigue. Upon further questioning, symptoms of dry eye and dry mouth became evident. Initial evaluation revealed hyperchloremic metabolic acidosis, severe hypokalem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 30 publications
0
15
0
3
Order By: Relevance
“…Patients with distal RTA typically develop hyperchloremic, hypokalemic metabolic acidosis with a normal anion gap [ 11 , 14 ]. In general, most patients develop hypokalemia as decreased distal secretion of H + via H + -ATPase or H + /K + -ATPase ultimately causes decreased K + reabsorption (i.e., renal K + wasting) [ 13 , 15 ]. If H + /K + -ATPase is primarily affected, then less K + will be reabsorbed.…”
Section: Classification Of Rtamentioning
confidence: 99%
“…Patients with distal RTA typically develop hyperchloremic, hypokalemic metabolic acidosis with a normal anion gap [ 11 , 14 ]. In general, most patients develop hypokalemia as decreased distal secretion of H + via H + -ATPase or H + /K + -ATPase ultimately causes decreased K + reabsorption (i.e., renal K + wasting) [ 13 , 15 ]. If H + /K + -ATPase is primarily affected, then less K + will be reabsorbed.…”
Section: Classification Of Rtamentioning
confidence: 99%
“…Hypokalemia may persist in some patients despite sustained correction of systemic acidosis with SoC alkali therapy [ 26 , 27 ] and these patients require potassium supplementation to maintain normal plasma potassium levels [ 28 ]. This justifies the treatment with potassium salts in ADV7103, which allows increasing plasma potassium without risk of hyperkalemia.…”
Section: Discussionmentioning
confidence: 99%
“…The exact pathophysiology by which autoimmune conditions cause dRTA is not completely understood and is likely a multifactorial process. Studies have indicated that the reduced secretion of hydrogen ions (H+) in patients with SS maybe because of the downregulated expression of vacuolar H+ATPase in Aintercalated cells of the distal renal tubules [15]. Immunoglobulin G (IgG) autoantibodies against different protein targets involved in acid secretion cells have also been reported, however, it remains unclear whether the antibodies trigger the initial damage or are formed as a result of exposure of intracellular epitopes to B cells from the preceding cell damage [15].…”
Section: Discussionmentioning
confidence: 99%